Penerapan Lean Manufacturing untuk Mereduksi Waste pada Proses Produksi Radius Chair di PT. Helie Furniture Indonesia - Mochammad Rizki Ramdani; Endang Prasetyaningsih; Mohamad Satori (UNISBA Press, 2022)
Abstract. PT. Helie Furniture Indonesia is a manufacturing company engaged in the furniture industry that produces several types of outdoor chairs made of stainless steel. This research focuses on one type of product, namely this product has the largest percentage of product delays compared to other products, which is 54.55%. In the production process of the radius chair, there are several wastes that exist in the production line, such as defective products and inventory in the form of work in process (WIP) found at the polishing work station. One approach that can reduce waste is Lean Manufacturing. The first step in this research is to find out waste using Value Stream Mapping (VSM) and Waste Assessment Model (WAM). Based on the results of WAM, 3 dominant wastes were obtained, namely defect, excess processing, and transport. Then the root cause of waste is carried out using 5 why's and determining the value of the Risk Priority Number (RPN) using Failure Mode and Effect Analysis (FMEA). The root cause of the problem in each dominant waste that has the highest RPN value will be made recommendations for improvement. There are 3 recommendations for improvement for supervision during the production process, SOP publication, and redesigning the layout on the production line. Recommendations for improvements that have been made can reduce lead time by 101.88 seconds and increase Process Cycle Efficiency (PCE) by 0.46%. Abstrak. PT. Helie Furniture Indonesia merupakan perusahaan manufaktur yang bergerak pada bidang industri furniture yang memproduksi beberapa jenis kursi outdoor berbahan baku stainless steel. Dalam penelitian ini berfokus pada salah satu jenis produk, yaitu produk radius chair karena produk ini memiliki persentase keterlambatan penyelesaian produk paling besar dibandingkan dengan produk kursi lainnya, yaitu sebesar 54,55%. Pada proses produksi radius chair terdapat beberapa waste yang ada pada lini produksi, seperti adanya produk cacat dan adanya penumpukan inventory berupa work in process (WIP) yang ditemui pada stasiun kerja polishing. Salah satu pendekatan yang dapat mereduksi waste adalah Lean Manufacturing. Langkah awal yang dilakukan pada penelitian ini adalah identifikasi waste menggunakan Value Stream Mapping (VSM) dan Waste Assessment Model (WAM). Berdasarkan hasil WAM, didapat 3 waste dominan yaitu defect, excessive processing, dan transportation. Kemudian dilakukan identifikasi akar penyebab waste menggunakan 5 why’s dan menentukan nilai Risk Priority Number (RPN) menggunakan Failure Mode and Effect Analysis (FMEA). Akar penyebab masalah pada setiap waste dominan yang memiliki nilai RPN tertinggi akan dibuat rekomendasi perbaikan. Terdapat 3 rekomendasi perbaikan yaitu Memperketat pengawasan selama proses produksi berlangsung, Publikasi SOP, dan Merancang ulang layout pada lini produksi. Rekomendasi perbaikan yang telah dibuat dapat mereduksi lead time sebesar 101,88 detik dan meningkatkan Process Cycle Efficiency (PCE) sebesar 0,46%.